Dissipation rate of acetamiprid in sweet cherries - Lazić, Sanja D; Šunjka, Dragana B; Panić, Srđan Z; Inđić, Dušanka V; Grahovac, Nada; Guzsvány, Valéria J; Jovan, Pavle (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Degradation of acetamiprid in sweet cherry samples was evaluated at several intervals from the product application until the end of the pre-harvest interval. An orchard of sweet cherries located at Stepanovićevo village near Novi Sad was used in this study. Acetamiprid was applied according to the manufacturer’s recommendation for protecting sweet cherries from their most important pests. Sweet cherry fruit samples were collected at eight intervals: immediately after acetamiprid application and 2, 4, 6, 8, 10, 12 and 14 days after application. The extraction of acetamiprid from sweet cherry samples was performed using a QuEChERS-based method. Determination was carried out using an HPLC-UV diode array detection system (Agilent 1100, United States) with an Agilent Zorbax Eclipse C18 column (50 mm × 4.6 mm internal diameter, 1.8 μm particle size). The method was subjected to a thorough validation procedure. The recovery data were obtained by spiking blank sweet cherry samples at three concentration levels (0.1-0.3 mg/kg), yielding 85.4% average recovery. Precision values expressed as relative standard deviation (RSD) were below 1.61% for the intraday precision. Acetamiprid showed linear calibrations from 0.05 to 2.5 μg/ml with correlation coefficient (R2) of 0.995%. The limit of detection and limit of quantification were found to be 5 μg/kg and 14 μg/kg, respectively. The validated method was applied in the analysis of acetamiprid in sweet cherry samples. During the study period, the concentration of acetamiprid decreased from 0.529 mg/kg to 0.111 mg/kg. The content of acetamiprid in sweet cherry samples at the end of the pre-harvest interval was below the maximum permissible level specified by the Serbian and EU MRLs.